Bulk-phase sulfur-doped zinc ferrite photo-anode as well as preparation method and application thereof

By doping sulfur in the zinc ferrite photoanode and performing specific treatment, the bulk phase sulfur-doped zinc ferrite photoanode was prepared, which solved the problem of low performance of zinc ferrite photoanode and significantly improved the photoelectrochemical water oxidation performance , suitable for industrial applications of photoelectrochemical decomposition of water.

CN119433606AActive Publication Date: 2025-02-14UNIV OF SCI & TECH OF CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411621418.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The performance of existing zinc ferrite (ZnFe2O4) photoanodes in photoelectrochemical decomposition of water is much lower than theoretically expected, mainly due to its low electron mobility and slow water oxidation kinetics.

Method used

The bulk sulfur-doped zinc ferrite photoanode is prepared by doping sulfur in the zinc ferrite photoanode and combining hydrothermal reaction and solid phase reaction, and the sulfur on the surface is removed by electrochemical treatment under light, retaining the sulfur. sulfur in the body phase.

Benefits of technology

The photoelectrochemical water oxidation performance has been significantly improved, and the photocurrent density at the water decomposition potential of 1.23 VRHE is increased by 81 times, from 5.4 μA·cm-2 to 0.44 mA·cm-2. The material is stable and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433606A_ABST
    Figure CN119433606A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photoelectrochemical water decomposition, in particular to a bulk-phase sulfur-doped zinc ferrite photo-anode and a preparation method and application thereof. The preparation method of the bulk-phase sulfur-doped zinc ferrite photo-anode comprises the following steps: S1) placing a conductive substrate in a mixed solution of an iron-containing compound and urea, and carrying out a hydrothermal reaction to obtain a beta-FeOOH nanorod array template; s2) under a heating condition, dropwise adding excessive zinc nitrate solution to the surface of the beta-FeOOH nanorod array template, then carrying out solid-phase reaction at high temperature, cooling to obtain zinc ferrite with the surface covered by zinc oxide, and removing the zinc oxide covered on the surface to obtain a zinc ferrite photo-anode; s3) soaking the zinc ferrite photo-anode in a solution of a sulfur-containing compound for anion exchange reaction to obtain a sulfur-doped zinc ferrite photo-anode, and S4) performing electrochemical treatment on the sulfur-doped zinc ferrite photo-anode under illumination to obtain the bulk-phase sulfur-doped zinc ferrite photo-anode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoelectrochemical water decomposition, and in particular to a bulk sulfur-doped zinc ferrite photoanode, a preparation method and application thereof. Background Art

[0002] In order to solve the environmental pollution and possible energy depletion caused by the continuous development and utilization of fossil fuels, it is increasingly urgent to find alternative green clean energy. Hydrogen energy, as an ideal clean energy, can replace fossil fuels to a certain extent due to its wide application, thereby alleviating the above problems. Photoelectrochemical water splitting can use photoelectrocatalytic materials to convert solar energy into clean energy - hydrogen energy, which is one of the effective ways to alleviate the energy crisis and environmental pollution.

[0003] In recent years, spinel ferrite (MFe2O4, M = Zn, Mg, Cu, Ca, Co, Ni, etc.) has been widely used due to its narrow bandgap (E g =1.90~2.40 eV), rich reserves of constituent elements, and photochemical stability have attracted the attention of more and more researchers in the field of photoelectrocatalysis, and it is one of the photoelectrocatalytic materials with great development prospects. In particular, zinc ferrite (ZnFe2O4), which has n-type semiconductor properties, is often studied as a photoanode material due to its relatively narrow band gap (about 2.10 eV), suitable band structure, and excellent photochemical stability. However, its low electron mobility and slow water oxidation kinetics make its photoelectrochemical performance far lower than theoretical expectations, which greatly limits their practical application in photoelectric conversion devices. Therefore, developing effective ways to improve the photoelectrochemical performance of ZnFe2O4 is very important to promote the large-scale application of photoelectrochemical water splitting to produce hydrogen. Summary of the invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide a bulk sulfur-doped zinc ferrite photoanode, a preparation method and application thereof, wherein the prepared photoanode material has high photoelectrochemical water oxidation performance.

[0005] To achieve the above object, the present invention provides a method for preparing a bulk sulfur-doped zinc ferrite photoanode, comprising the following steps:

[0006] S1) placing a conductive substrate in a mixed solution of an iron compound and urea to perform a hydrothermal reaction to obtain a β-FeOOH nanorod array template;

[0007] S2) under heating conditions, adding an excess of zinc nitrate solution to the surface of the β-FeOOH nanorod array template, and then performing a solid phase reaction at high temperature, and obtaining zinc ferrite with zinc oxide covering the surface after cooling, and obtaining the zinc ferrite photoanode ZnFe2O4 after removing the zinc oxide covering the surface;

[0008] S3) immersing the zinc ferrite photoanode in a solution containing a sulfur compound to perform an anion exchange reaction to obtain a sulfur-doped zinc ferrite photoanode;

[0009] S4) electrochemically treating the sulfur-doped zinc ferrite photoanode under light to remove the sulfur on the surface and retain the sulfur in the bulk phase to obtain a bulk sulfur-doped zinc ferrite photoanode ZnFe2O 4-x S x .

[0010] The above-mentioned bulk phase refers to the interior of the material.

[0011] In the step S1), the iron-containing compound is preferably ferric chloride hexahydrate or ferric nitrate nonahydrate.

[0012] The molar ratio of the iron-containing compound to urea is preferably 0.1-1:1, more preferably 1:1.

[0013] The temperature of the hydrothermal reaction is preferably 80-120°C, more preferably 100°C.

[0014] The hydrothermal reaction time is 4 to 8 h, more preferably 6 h.

[0015] The present invention has no special limitation on the conductive substrate, and it can be a suitable conductive substrate well known to those skilled in the art. Preferably, the conductive substrate is FTO conductive glass.

[0016] Preferably, the conductive substrate is cleaned with solvents such as acetone and anhydrous ethanol before the hydrothermal reaction.

[0017] Preferably, in the present invention, during the hydrothermal reaction, the non-conductive surface of the conductive substrate is placed against the wall of the reaction bottle, so that the hydrothermal reaction can be better carried out on the conductive surface.

[0018] In the step S2), the heating temperature is preferably 80-120°C.

[0019] The concentration of the zinc nitrate solution is preferably 0.010-0.10 mol / L, more preferably 0.10 mol / L.

[0020] The temperature of the solid phase reaction is preferably 450-700°C, more preferably 600°C.

[0021] The solid phase reaction time is preferably 20 to 40 min, more preferably 20 min.

[0022] The solid phase reaction is preferably carried out in a tube furnace.

[0023] The solid phase reaction is preferably carried out in an air atmosphere.

[0024] In the step S2), the method for removing the zinc oxide covered on the surface is preferably: immersing the zinc ferrite with the zinc oxide covered on the surface in an alkaline solution.

[0025] The alkaline compound in the alkaline solution preferably includes one or more of sodium hydroxide and potassium hydroxide.

[0026] The concentration of the alkaline solution is preferably 4-7 mol / L, more preferably 5 mol / L.

[0027] The soaking time is preferably 2 to 5 h, specifically 2 h, 3 h or 4 h, more preferably 3 h.

[0028] In the step S3), the sulfur-containing compound is preferably sodium sulfide nonahydrate.

[0029] The concentration of the solution of the sulfur-containing compound is preferably 0.1-1.0 mol / L, more preferably 0.1 mol / L.

[0030] The temperature of the anion exchange reaction is preferably 80-120°C, more preferably 100°C.

[0031] The anion exchange reaction time is preferably 4 to 8 h, specifically 4 h, 6 h or 8 h, more preferably 6 h.

[0032] In the step S4), the electrochemical treatment under illumination is a cyclic voltammetry test under illumination.

[0033] Preferably, the electrolyte used in the cyclic voltammetry test is a 0.5-3 mol / L NaOH solution, more preferably a 1 mol / L NaOH solution; preferably, the voltage range of the cyclic voltammetry test is -0.4-0.8 V, more preferably -0.5-0.6 V; preferably, the number of cycles is 5-20 times, more preferably 20 times; preferably, the illumination condition is provided by a simulated light source, and the simulated light source used is preferably a 300 W xenon lamp in combination with an AM 1.5G filter; preferably, the light source intensity is 50-300 mW / cm 2 , more preferably 100 mW / cm 2 .

[0034] The method of the present invention can prepare a bulk sulfur-doped zinc ferrite photoanode with greatly improved photoelectrochemical water oxidation performance through a simple and unique synthesis method. The obtained photoanode material has good stability and a water decomposition potential of 1.23 V. RHE The photocurrent density at the -2Increased to 0.44 mA·cm -2 The synthesis method of the present invention is simple, and the obtained photoanode material is easy to use, which is conducive to popularization and application in industrial production.

[0035] The present invention provides a bulk sulfur-doped zinc ferrite photoanode material prepared by the above preparation method, comprising zinc ferrite as a main body of a photoelectric catalyst and sulfur element for modification.

[0036] The morphology of the bulk sulfur-doped zinc ferrite photoanode material is a nanorod array, and the length of the nanorod is 400-500 nm and the diameter is 30-50 nm.

[0037] The photoelectrochemical activity test results show that the photoelectrochemical water oxidation performance of the bulk sulfur-doped zinc ferrite photoanode material provided by the present invention is significantly improved.

[0038] Based on this, the present invention provides a method for preparing the above-mentioned bulk sulfur-doped zinc ferrite photoanode material and the above-mentioned bulk sulfur-doped zinc ferrite photoanode material and its application in photoelectrochemical water decomposition reaction.

[0039] Preferably, the temperature of the photoelectrochemical water splitting reaction is room temperature; the electrolyte used in the reaction is NaOH solution; the simulated light source used in the reaction is a 300 W xenon lamp with an AM 1.5G filter; the intensity of the light source is preferably 50-300 mW / cm 2 , more preferably 100 mW / cm 2 The concentration of the NaOH solution is preferably 0.5-3 mol / L, more preferably 1 mol / L.

[0040] In some specific embodiments of the present invention, the application method is as follows: a three-electrode system is used, wherein the counter electrode is a platinum electrode, the reference electrode is a silver / silver chloride electrode, and the working electrode is the above-mentioned bulk sulfur-doped zinc ferrite photoanode material; the electrolyte is a 1 mol / L sodium hydroxide solution. Photoelectrochemical related tests are carried out in a quartz reaction cell under light.

[0041] Specifically, the bulk sulfur-doped zinc ferrite photoanode is first placed on an electrode clip as a working electrode, and then a silver / silver chloride electrode and a platinum electrode are inserted in sequence and connected to the three electrode clips of the electrochemical workstation. Then, an appropriate amount of 1 mol / L sodium hydroxide solution is added to the quartz reaction cell. The xenon lamp light source is vertically irradiated on the working electrode area, and the light intensity is guaranteed to be one sunlight intensity (100 mW / cm 2 ), and then prepare to start the relevant photoelectrochemical tests.

[0042] The present invention provides a method for preparing the bulk sulfur-doped zinc ferrite photoanode and the bulk sulfur-doped zinc ferrite photoanode material and application thereof in photoelectrochemical water decomposition.

[0043] Compared with the prior art, the present invention provides a method for preparing a bulk sulfur-doped zinc ferrite photoanode, comprising the following steps: S1) placing a conductive substrate in a mixed solution of an iron-containing compound and urea, and performing a hydrothermal reaction to obtain a β-FeOOH nanorod array template; S2) under heating conditions, dripping an excess of zinc nitrate solution onto the surface of the β-FeOOH nanorod array template, and then performing a solid-phase reaction at high temperature, and obtaining zinc ferrite with zinc oxide covered on the surface after cooling, and obtaining a zinc ferrite photoanode after removing the zinc oxide covered on the surface; S3) immersing the zinc ferrite photoanode in a solution of a sulfur-containing compound, and performing an anion exchange reaction to obtain a bulk sulfur-doped zinc ferrite photoanode; S4) performing an electrochemical treatment under light on the sulfur-doped zinc ferrite photoanode to remove sulfur on the surface, retain sulfur in the bulk phase, and obtain a bulk sulfur-doped zinc ferrite photoanode. The present invention can prepare a bulk sulfur-doped zinc ferrite photoanode with greatly improved photoelectrochemical water oxidation performance through a simple and unique synthesis method, and the obtained photoanode has good stability and a water decomposition potential of 1.23 V. RHE The photocurrent density at the -2 Increased to 0.44 mA·cm -2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The photoanode is the zinc ferrite (ZnFe2O4) prepared in Example 1 and the bulk sulfur-doped zinc ferrite (ZnFe2O 4-x S x ) Scanning electron microscope (SEM) image of the photoanode;

[0045] Figure 2 The zinc ferrite (ZnFe2O4) photoanode prepared in Example 1 and the ZnFe2O4 photoanode prepared in Example 2 4-x S x X-ray diffraction pattern of the photoanode;

[0046] Figure 3 ZnFe2O 4-x S x Performance diagram of photoelectrochemical water splitting of photoanode and comparative sample ZnFe2O4 photoanode. DETAILED DESCRIPTION

[0047] In order to further illustrate the present invention, the following is a detailed description in conjunction with the embodiments. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0048] All raw materials of the present invention are not particularly limited in their sources and can be purchased from the market or prepared according to conventional methods well known to those skilled in the art.

[0049] The following instruments are used in Examples 1 to 2:

[0050] Scanning electron microscope (USA FEI, Sirion200 Schottky field emission scanning electron microscope)

[0051] X-ray diffractometer (SmartLab multifunctional rotating target X-ray diffractometer, Rigaku Corporation, Japan)

[0052] Electrochemical workstation (CHI650E electrochemical analyzer, Chenhua, Shanghai, China)

[0053] Xenon lamp light source (China Zhongjiao Jinyuan, CEL-HXF300-T3 photocatalytic xenon lamp light source).

[0054] Example 1

[0055] Step 1: Preparation of zinc ferrite (ZnFe2O4) photoanode

[0056] β-FeOOH deposited on the surface of conductive glass was prepared by hydrothermal method. 20.27 g of ferric chloride hexahydrate and 4.50 g of urea were dissolved in 50 mL of deionized water, stirred evenly and transferred into a 500 mL volumetric flask. 30 mL of the solution was placed in a reagent bottle and the cleaned conductive glass FTO was placed in it with the back against the bottle wall. After sealing, it was placed in a homogeneous reactor and heated to 100 ° C for 6 h. After the reaction, the product was washed with deionized water and dried naturally to obtain a β-FeOOH nanorod array template. The β-FeOOH nanorod array template was placed on a heating table preheated to 100 ° C, an excess of 0.10 mol / L zinc nitrate solution was added, and after drying, it was placed in a preheated 600 ° C tube furnace, calcined for 20 min, cooled to room temperature, taken out, and immersed in 5 mol / L sodium hydroxide solution for 3 h to remove zinc oxide on the surface. Wash with deionized water and dry to obtain zinc ferrite (ZnFe2O4) photoanode.

[0057] Figure 1 Figure a in the middle is a scanning electron microscope (SEM) photograph of the prepared zinc ferrite (ZnFe2O4) photoanode; it can be seen that the prepared sample is in the shape of nanorods, with a length of about 400~500 nm, a diameter of about 30~50 nm, and is evenly distributed.

[0058] The X-ray diffraction patterns (XRD) of the prepared zinc ferrite (ZnFe2O4) photoanode samples are listed in Figure 2The prepared sample is compared with the standard XRD card (JCPDS NO.22-1012) and it is known that it is spinel ZnFe2O4.

[0059] Step 2: Evaluation of the photoelectrochemical water splitting activity of zinc ferrite (ZnFe2O4) photoanode

[0060] The obtained zinc ferrite (ZnFe2O4) was placed on the electrode clip as the working electrode, and then the silver / silver chloride electrode and the platinum electrode were inserted in sequence and connected to the three electrode clips of the electrochemical workstation. Then, an appropriate amount of 1 mol / L sodium hydroxide solution was added to the quartz reaction cell. The xenon light source was vertically irradiated on the working electrode area, and the light intensity was guaranteed to be one sun light intensity (100 mW / cm 2 ). Then the photoelectrochemical test was carried out. Under light illumination, the linear voltammetry test was carried out. The parameters were set as follows: scan speed: 25 mV / s; scan range: -0.50~0.60 V; sensitivity: 10 -3 .

[0061] The results are listed in Figure 3 . Figure 3 ZnFe2O 4-x S x JV curves of the photoanode and the comparative sample ZnFe2O4 photoanode. It can be seen that the water decomposition potential of the ZnFe2O4 photoanode is 1.23 V RHE The photocurrent density at -2 .

[0062] Example 2

[0063] Step 1: Preparation of zinc ferrite (ZnFe2O4) photoanode

[0064] β-FeOOH deposited on the surface of conductive glass was prepared by hydrothermal method. 20.27 g of ferric chloride hexahydrate and 4.50 g of urea were dissolved in 50 mL of deionized water, stirred evenly and transferred into a 500 mL volumetric flask. 30 mL of the solution was placed in a reagent bottle and the cleaned conductive glass FTO was placed in it with the back against the bottle wall. After sealing, it was placed in a homogeneous reactor and heated to 100 ° C for 6 h. After the reaction, the product was washed with deionized water and dried naturally to obtain a β-FeOOH nanorod array template. The β-FeOOH nanorod array template was placed on a heating table preheated to 100 ° C, an excess of 0.10 mol / L zinc nitrate solution was added, and after drying, it was placed in a tubular furnace preheated to 600 ° C. After calcination for 20 min, it was taken out after cooling to room temperature and immersed in 5 mol / L sodium hydroxide solution for 3 h to remove zinc oxide on the surface. Wash with deionized water and dry to obtain zinc ferrite (ZnFe2O4) photoanode.

[0065] Step 2: Bulk sulfur-doped zinc ferrite photoanode (ZnFe2O 4-x S x )

[0066] Dissolve 12.00 g of sodium sulfide nonahydrate in 50 mL of deionized water, stir evenly and transfer to a 500 mL volumetric flask, take 30 mL of the solution in a reagent bottle, place the ZnFe2O4 photoanode described in step 1 in it with its back against the bottle wall, seal it and place it in a homogeneous reactor and heat it to 100 °C for 6 h. After the reaction, wash the product with deionized water, dry it, and then perform a cyclic voltammetry test under light. After the treatment is completed, take it out, wash it, and dry it to obtain a bulk sulfur-doped zinc ferrite photoanode (ZnFe2O 4-x S x ).

[0067] Figure 1 Figure b shows the prepared bulk sulfur-doped zinc ferrite (ZnFe2O 4-x S x ) Scanning electron microscope (SEM) photoanode; it can be seen that the prepared ZnFe2O 4-x S x The sample still retains the nanorod array morphology, and the surface morphology of the nanorods has not changed significantly.

[0068] Prepared ZnFe2O 4-x S x The X-ray diffraction pattern (XRD) of the photoanode is listed in Figure 2 The comparison between the prepared sample and the standard XRD card (JCPDS NO.22-1012) shows that it is spinel ZnFe2O4. The S treatment does not produce any new diffraction peaks, indicating that its crystal phase has not been changed.

[0069] Step 3: Bulk sulfur-doped zinc ferrite photoanode (ZnFe2O 4-x S x ) for photoelectrochemical water splitting

[0070] Similar to step 2 in Example 1, the obtained ZnFe2O 4-x S x The photoanode is placed on the electrode clip as the working electrode, and then the silver / silver chloride electrode and the platinum electrode are inserted in sequence and connected to the three electrode clips of the electrochemical workstation. Then add an appropriate amount of 1 mol / L sodium hydroxide solution to the quartz reaction cell. Ensure that the xenon light source is vertically irradiated on the working electrode area, and the light intensity is guaranteed to be one sun light intensity (100 mW / cm 2). Then the photoelectrochemical test was carried out. Under light illumination, the linear voltammetry test was carried out. The parameters were set as follows: scan speed: 25 mV / s; scan range: -0.50~0.60 V; sensitivity: 10 -3 .

[0071] The results are listed in Figure 3 . Figure 3 ZnFe2O 4-x S x JV curves of the photoanode and the comparative sample ZnFe2O4 photoanode. It can be seen that ZnFe2O 4-x S x Photoanode water decomposition potential 1.23 V RHE The photocurrent density at -2 The water decomposition potential of zinc ferrite photoanode was 1.23 V after anion exchange and light cyclic voltammetry. RHE The photocurrent density at the -2 Increased to 0.44 mA·cm -2 .

[0072] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a bulk sulfur-doped zinc ferrite photoanode, comprising the following steps: S1) placing a conductive substrate in a mixed solution of an iron compound and urea to perform a hydrothermal reaction to obtain a β-FeOOH nanorod array template; S2) under heating conditions, adding an excess of zinc nitrate solution to the surface of the β-FeOOH nanorod array template, and then performing a solid phase reaction at high temperature, and obtaining zinc ferrite with zinc oxide covering the surface after cooling, and obtaining the zinc ferrite photoanode ZnFe2O4 after removing the zinc oxide covering the surface; S3) immersing the zinc ferrite photoanode in a solution containing a sulfur compound to perform an anion exchange reaction to obtain a sulfur-doped zinc ferrite photoanode; S4) electrochemically treating the sulfur-doped zinc ferrite photoanode under light to remove the sulfur on the surface and retain the sulfur in the bulk phase to obtain a bulk sulfur-doped zinc ferrite photoanode ZnFe2O 4-x S x .

2. The preparation method according to claim 1, characterized in that: The iron-containing compound is ferric chloride hexahydrate or ferric nitrate nonahydrate; The molar ratio of the iron-containing compound to urea is 0.1 to 1:1; The temperature of the hydrothermal reaction is 80-120°C, and the time of the hydrothermal reaction is 4-8h; The conductive substrate is FTO conductive glass.

3. The preparation method according to claim 1, characterized in that: In the step S2), the heating temperature is 80-120°C; The concentration of the zinc nitrate solution is 0.010-0.10 mol / L; The temperature of the solid phase reaction is 450-700°C; The solid phase reaction time is 20 to 40 min.

4. The preparation method according to claim 1, characterized in that: In the step S2), the method for removing the zinc oxide covered on the surface is: soaking the zinc ferrite with the zinc oxide covered on the surface in an alkaline solution; The alkaline compound in the alkaline solution includes one or more of sodium hydroxide and potassium hydroxide; The concentration of the alkaline solution is 4-7 mol / L; The soaking time is 2 to 5 hours.

5. The preparation method according to claim 1, characterized in that: In the step S3), the sulfur-containing compound is selected from sodium sulfide nonahydrate; The concentration of the solution of the sulfur-containing compound is 0.1-1.0 mol / L; The temperature of the anion exchange reaction is 80-120°C; The anion exchange reaction time is 4 to 8 h.

6. The preparation method according to claim 1, characterized in that: In the step S4), the electrochemical treatment under illumination is a cyclic voltammetry test under illumination; the illumination condition is provided by a simulated light source, and the simulated light source is a 300 W xenon lamp in combination with an AM 1.5G filter; the intensity of the light source is 50-300 mW / cm 2 ; The cyclic voltammetry test electrolyte is 0.5~3 mol / L NaOH solution; The cyclic voltammetry test voltage range is -0.4~0.8 V; The number of cycles of the cyclic voltammetry test is 5 to 20 times.

7. The bulk sulfur-doped zinc ferrite photoanode material prepared by the preparation method according to any one of claims 1 to 6 comprises zinc ferrite as a main photoelectrocatalyst and sulfur element for modification.

8. The bulk sulfur-doped zinc ferrite photoanode material according to claim 7, characterized in that: The morphology of the bulk sulfur-doped zinc ferrite photoanode material is a nanorod array, and the length of the nanorod is 400-500 nm and the diameter is 30-50 nm.

9. Use of the bulk sulfur-doped zinc ferrite photoanode material prepared by the preparation method according to any one of claims 1 to 6 or the bulk sulfur-doped zinc ferrite photoanode material according to any one of claims 7 to 8 in photoelectrochemical water decomposition reaction.

10. The use according to claim 9, characterized in that: The temperature of the photoelectrochemical water splitting reaction is room temperature; the electrolyte used in the reaction is NaOH solution; the simulated light source used in the reaction is a 300 W xenon lamp with an AM 1.5G filter; the intensity of the light source is 50~300mW / cm 2 .

Citation Information

Patent Citations

  • Composite photocatalyst, and preparation method and application thereof

    CN112934233A

  • Novel zinc ferrite and nickel doped zinc-indium-sulfur heterojunction photoelectrocatalytic anode material and preparation method thereof

    CN114768831A

  • Zinc ferrite photoanode with ultralow water oxidation photocurrent initial potential, preparation method and application

    CN114921806A